Nieznane źródła „Historii kościelnej" Ewagriusza Scholastyka (HE III 30) - Ginter, Kazimierz (Vox Patrum, 2000)
Evagrius Scholasticus, the author of Historia Ecclesiastica, written at the end of the sixth century, is unanimously regarded by scholars as a person - in proportion to his times - of broad horizons and objectivity. He is without any doubt an unusual writer. A good example of his originality is his description of the rule emperor Anastasius. Evagrius describes him very warmly, although the emperor was regarded as a partisan of the monophysites. Yet Evagrius, without any doubt a Chalcedonian writer, places Anastasius in heaven after his death; Justinian, on the other hand, is placed in hell.